Work -Nonwork Boundary Management Preferences and Well - Being Among Nurses: Family-Supportive Supervisor Behavior as a Moderator - Natalia, Carlina; Bandar, Nur Fatihah Abdullah; Balang, Rekaya Vincent; Hassan, Zaiton; Ibrahim, Dayang Kartini Abang; Ahamad, Rusli; Hamidi, Hana (International Journal of Psychosocial Rehabilitation, 2020)
The issue of managing the balance between the context of work and life among nurses is an evident fact in Malaysia, which potentially was due to the job nature of nurses and one’s own personal commitments. Boundary management is a method in which people use to address their work-life balance condition leading to better wellbeing. Furthermore, family supportive supervisor behavior pose to be a moderator in which helps to support nurses in successfully manging their boundaries. Deriving from the intention to obtain a more concrete finding on whether supportive supervisor behaviour can help nurses attain better boundary management, the aim of the study focuses on examining the moderating effect of family-supportive supervisor behavior on the relationship between work-nonwork boundary management preferences and well-being among nurses. Questionnaires were administered to registered nurses in a private hospital in Kuching, Sarawak with 67 responses collected and the data was being analysed using IBM SPSS 25. Results revealed there is no significant relationship between work-nonwork boundary preferences and well-being. Family-supportive supervisor behavior was positively related to well-being among nurses. The result revealed that family-supportive supervisor behavior moderates the relationship between work-nonwork boundary management preferences and well-being among nurses. Based on our findings, family-supportive supervision is a plausible boundary condition for the relationship between work-nonwork boundary preferences and well-being. This study suggests that, family-supportive supervision is a trainable resource that organizations should facilitate to improve employee well-being in healthcare settings.